NARCOTICS ABUSE AT THE BENGKULU CITY CLASS II A PENITENTIARY INSTITUTIONS - Guslaini Guslaini; Antory Royan Adyan; Herlambang Herlambang (Bengkoelen Justice : Jurnal Ilmu Hukum, 2022)
The objectives of this research were: (1). How was the application of sanctions against officers involved in narcotics abuse at the Bengkulu City Class II A Penitentiary Institutions (2) What were the obstacles to overcoming officers involved in narcotics abuse at the Bengkulu City Class II A Penitentiary Institutions? (3) What were the efforts to overcome officers involved in narcotics abuse at the Bengkulu City Class II A Penitentiary Institutions. In this thesis research method, the type of research used was descriptive. This type of research in legal research includes empirical legal research. The results of the study are: (1) the application of sanctions against officers involved in narcotics abuse at the Bengkulu City Class II A Penitentiary Institutions, for Penitentiary institutions officers involved in the narcotics distribution network will be sentenced to imprisonment according to Law Number 35 of 2009 concerning Narcotics; the warden must be subject to criminal sanctions and fines; and administrative sanctions according to the Regulation of the Minister of Law and Human Rights Number M. HH.16. KP. 05.02 of 2011 regarding the Code of Ethics for Penitentiary officers, the warden is subject to administrative sanctions, namely being dismissed as a penitentiary officer (there has been an inkracht decision). (2) The difficulties in collecting evidence to prove officers involved in narcotics abuse at the Bengkulu City Class II A Penitentiary Institutions are: difficulties in collecting evidence to prove; the supervision system in the penitentiary institution is not yet maximized; the number of wardens at the Bengkulu City Class II A penitentiary institution is not comparable to prisoners; the number of narcotics addicts who are only imprisoned without being rehabilitated; the human resources (3) Efforts to overcome officers involved in narcotics abuse at the Class II A Penitentiary Institution in Bengkulu City are: collecting data on prisoners and penitentiary officers who have used or are involved in narcotics problems; improving facilities and infrastructure; increasing the human resources of the Class II A penitentiary Institution officers in Bengkulu City, coaching for prisoners and officers of the Bengkulu City Class II A Penitentiary Institution who have been involved in narcotics problems.